1959
DOI: 10.1038/bjc.1959.73
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pseudopregnancy on the Induction of Mammary Tumours by Methylcholanthrene in Mice of the Balb/c Strain

Abstract: MAMMARY carcinomas can be induced in virgin IF female mice by means of chemical carcinogens (Bonser, 1958). But it was shown by Bonser (1954) that oestrogen alone was not a sufficient substitute for the ovaries as the hormonal stimulus in the induction of such tumours by methylcholanthrene. However, by replacement of the ovarian steroid hormones by oestrogen and progesterone, Jull (1954) was able to obtain 9 tumours in 11 ovariectomised mice. He also demonstrated (1953) that virgin females of this strain have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

1962
1962
1968
1968

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 1 publication
2
18
1
Order By: Relevance
“…In this connection, it is of interest that the unexpected appearance of a breast tumour in the last survivor of the pseudopregnant group of C57B1 treated with DAIBA was associated with a large ovarian tumour, which may have been the source of the hormonal stimulation required for its development. The C3Hb virgin female mice used by Biancifiori et al (1961) might have been expected, on Jull's (1956) hypothesis, to be rather insensitive to breast tumour iniduction bv DMBA and MC, since they have a rather low incidence of spontaneous pseudopregnancy. They were, however, found to be fairly sensitive to these carcinogens, both of which produced a good yield of granulosa-celled tumours of the ovaries, at about the same time as the development of the mammarv tumours.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this connection, it is of interest that the unexpected appearance of a breast tumour in the last survivor of the pseudopregnant group of C57B1 treated with DAIBA was associated with a large ovarian tumour, which may have been the source of the hormonal stimulation required for its development. The C3Hb virgin female mice used by Biancifiori et al (1961) might have been expected, on Jull's (1956) hypothesis, to be rather insensitive to breast tumour iniduction bv DMBA and MC, since they have a rather low incidence of spontaneous pseudopregnancy. They were, however, found to be fairly sensitive to these carcinogens, both of which produced a good yield of granulosa-celled tumours of the ovaries, at about the same time as the development of the mammarv tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Such waning may be due to the age of the mice, or to the effect of the carcinogen treatment on their ovaries. Of the 4 carcinogens used, DMBA is known to have by far the greatest effect upon mouse ovaries (Mody 1960Biancifiori et al 1961. It rapidly causes the destruction of oocytes and this is followed by the disappearance of the corpora lutea (Marchant, 1959).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jull (1958) reported an incidence of 43 per cent in virgin IF mice given 4 fortnightly skin applications of an 0-25 per cent solution of this compound in arachis oil, and Biancifiori et al (1961) found 4 breast tumours in 15 virgin female C3Hb mice treated 8 times at weekly intervals by skin painting, but none arose in 15 mice treated for 8 weeks with the carcinogen by stomach tube.…”
Section: Discussionmentioning
confidence: 99%